Individual-Oriented Relationship Education: Exploring Adverse Childhood Experiences as a Moderator of Individual Distress Outcomes. Issue 1 (2nd January 2020) - Wheeler, Naomi J.; Griffith, Sandy-Ann M.; Harris, Shaywanna; Kozachuk, Lindsay A.
Abstract: Indicators of social and economic risk moderate outcomes of couple-formats of relationship education (RE); yet, less is known about moderators of individual-oriented formats or risk associated with childhood adversity. Adverse childhood experiences (ACE) influence well-being including relational, physical, and mental health. The current study examined the influence of ACE for changes in distress for participants ( N  = 223) who completed an individual-oriented RE intervention. Results demonstrate ACE as a significant moderator of change, where the 'four or more' ACE group reported the highest distress at baseline and benefited most. Implications for RE practice and research are discussed.